THE EFFECT OF PROVIDING GOAT MANURE AND ADDITIN WATER WITH THE PARTIAL ROOT ZONE (PRD) METHOD IN INCREASING THE GROWTH AND PRODUCTION OF TOMATO PLANTS (LYCOPERSICUM ESCULENTUM MILL) USING A DIGITAL SOIL MOISTURE METER IN NORTH SUMATERA - Idris, M.; Selvia, Irda Nila; Ong, Russell; Armansyah, Armansyah; Kamarudin, Mohd Khairul Amri (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2025)
This study aims to investigate the effectiveness of the Partial Rootzone Drying (PRD) irrigation method, the application of goat manure as organic fertilizer, and the interaction of both treatments on the growth and yield of tomato plants (Lycopersicum esculentum Mill) in North Sumatra. The research responds to the urgent need for sustainable agricultural practices that conserve water and enhance soil fertility, especially in tropical regions facing irregular rainfall and declining soil quality. A field experiment was conducted using a factorial randomized block design to test various levels of goat manure combined with the PRD technique. Observations focused on vegetative growth parameters (plant height, number of leaves, dry weight, chlorophyll content, Relative Growth Rate), nutrient uptake (N, P, and K), and production indicators (fruit number and sugar content). Data were analyzed statistically to determine the significance and interaction effects of treatments. The results show that goat manure significantly improves vegetative growth and fruit production, with higher doses correlating positively to increases in biomass and nutrient uptake. The PRD method led to a 25% reduction in water use without compromising plant productivity. Importantly, the combination of PRD and organic manure application produced synergistic effects, enhancing both growth and yield while optimizing water and nutrient efficiency. This study introduces a novel integrated approach to tomato cultivation that combines precision irrigation (PRD) and organic soil enrichment, offering a replicable model for sustainable, water-efficient horticulture in resource-constrained agricultural regions.